Ensete ventricosum: A Multipurpose Crop against Hunger in Ethiopia - Getahun Yemata (The Scientific World Journal)
Ensete ventricosum is a traditional multipurpose crop mainly used as a staple/co-staple food for over 20 million people in Ethiopia. Despite this, scientific information about the crop is scarce. Three types of food, viz., Kocho (fermented product from scraped pseudostem and grated corm), Bulla (dehydrated juice), and Amicho (boiled corm) can be prepared from enset. These products are particularly rich in carbohydrates, minerals, fibres, and phenolics, but poor in proteins. Such meals are usually served with meat and cheese to supplement proteins. As a food crop, it has useful attributes such as foods can be stored for long time, grows in wide range of environments, produces high yield per unit area, and tolerates drought. It has an irreplaceable role as a feed for animals. Enset starch is found to have higher or comparable quality to potato and maize starch and widely used as a tablet binder and disintegrant and also in pharmaceutical gelling, drug loading, and release processes. Moreover, enset shows high genetic diversity within a population which in turn renders resilience and food security against the ever-changing environmental factors and land use dynamics. Therefore, more research attention and funding should be given to magnify and make wider use of the crop.